2017
DOI: 10.1002/cctc.201700972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction Treatment on CO Oxidation with CeO2 Nanorod‐Supported CuOx Catalysts

Abstract: Understanding the correlation of thermal treatment with catalyst activity provides mechanistic information about how the catalysts can be activated or deactivated. In this paper, we report that a comparative study was conducted on CeO2 nanorod‐supported CuOx catalysts before and after reduction treatment to gain insight on the effects of the copper oxidation state and catalyst–support interfacial interactions on CO oxidation. X‐ray diffraction, Raman spectroscopy, hydrogen temperature‐programmed reduction (H2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Besides the advances that can be induced by adjusting the size, shape and electronic state of MOs, special pretreatment protocols or activation procedures could be applied to further adjust the local surface chemistry of MOs (e.g., [200,201]). In particular, the local surface chemistry of the MOs can be further tailored by appropriate pretreatment protocols, including thermal or chemical pretreatment.…”
Section: Pretreatment Effectsmentioning
confidence: 99%
“…Besides the advances that can be induced by adjusting the size, shape and electronic state of MOs, special pretreatment protocols or activation procedures could be applied to further adjust the local surface chemistry of MOs (e.g., [200,201]). In particular, the local surface chemistry of the MOs can be further tailored by appropriate pretreatment protocols, including thermal or chemical pretreatment.…”
Section: Pretreatment Effectsmentioning
confidence: 99%
“…Some reports in the literature have demonstrated that CeO 2 ‐based oxides are good catalysts for CO oxidation . Herein, CO conversion as a function of the reaction temperature for the catalysts is shown in the Figure .…”
Section: Resultsmentioning
confidence: 98%
“…[31] Some reports in the literatureh ave demonstrated that CeO 2based oxides are good catalysts for CO oxidation. [32][33][34] Herein, CO conversion as af unctiono ft he reaction temperature for the catalysts is shown in the Figure 7. The conversion of CO that reaches 50 %( T 50 )i su sed to evaluate the catalytic activity of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…The strong band at ca. [37,53,55,68,69] Interestingly, the absence of Raman peaks (at ca. [59][60][61] According to several studies, this band appears at ca.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…1174 cm À 1 are linked with the presence of oxygen vacancies and/or defects in the CeO 2 structure. [37,53,55,68,69] Interestingly, the absence of Raman peaks (at ca. 295 cm À 1 and ca.…”
Section: Physicochemical Characterizationmentioning
confidence: 99%